2021
DOI: 10.3390/life11101026
|View full text |Cite
|
Sign up to set email alerts
|

Post-Mastectomy Pain: An Updated Overview on Risk Factors, Predictors, and Markers

Abstract: After breast surgery, women frequently develop chronic post-mastectomy pain (PMP). PMP refers to the occurrence of pain in and around the area of the mastectomy lasting beyond three months after surgery. The nature of factors leading to PMP is not well known. When PMP is refractory to analgesic treatment, it negatively impacts the lives of patients, increasing emotional stress and disability. For this reason, optimizing the quality of life of patients treated for this pathology has gained more importance. On t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 71 publications
(79 reference statements)
1
10
0
Order By: Relevance
“…In 2006, a study showed that youth was often considered a predictor of postoperative pain [39]. Recent studies also show that younger breast cancer patients are more likely to develop PMPS than older breast cancer patients [40][41][42]. In our study, patients in the PMPS group were also younger than those in the non-PMPS group.…”
Section: Agesupporting
confidence: 55%
“…In 2006, a study showed that youth was often considered a predictor of postoperative pain [39]. Recent studies also show that younger breast cancer patients are more likely to develop PMPS than older breast cancer patients [40][41][42]. In our study, patients in the PMPS group were also younger than those in the non-PMPS group.…”
Section: Agesupporting
confidence: 55%
“…More extensive tissue injury might lead to higher levels of postoperative systemic inflammatory markers. For example, inflammatory mechanisms may be implicated in a higher likelihood of post-mastectomy pain syndrome, contributing to morbidity in these patients 21 . The extent to which post-surgical increased inflammation leads to greater post-adjuvant therapy persistent symptoms (i.e., following chemotherapy, radiation, or endocrine therapy) is an area in need of further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published review of studies assessed various treatment modalities for chronic pain after breast cancer surgery, including physical and psychological approaches as well as pharmacological (e.g., anti-depressants, anti-convulsants, topical analgesic creams) and interventional strategies (e.g., PEC I or II blocks, serratus plane blocks, neuromodulation). However, high-quality evidence of beneficial interventions is lacking, stressing the need to identify novel treatments and, more importantly, find ways to prevent this type of pain from occurring [16,60,61].…”
Section: Discussionmentioning
confidence: 99%